Competition policy in healthcare : frontiers in insurance-based and taxation-funded systems / Mary Guy. - Guy, Mary (Law professor) (Intersentia, 2019)
This book brings a unique, comparative approach to competition policy in healthcare. By examining an insurance-based and a taxation-funded healthcare system, insights emerge into the applicability and application of general competition law and healthcare-specific competition rules at EU and Member State level. The developing interactions between healthcare regulators and competition authorities, and issues arising from hospital mergers with regard to general and healthcare-specific merger control both receive in-depth analysis. Insights into competition reforms in the Dutch and English healthcare systems show that the term "healthcare" is problematic: there are important distinctions between public and private healthcare, and between healthcare providers and healthcare purchasers. Even a focus on "healthcare providers" has limitations given the myriad services which comprise healthcare delivery. Competition reforms in healthcare attract controversy if seen exclusively as an end in themselves. This book argues that a nuanced approach is needed: competition in healthcare needs to be tempered, and even focused, by national and EU commitments to solidarity. Following Brexit, scholars and policy makers will maintain interest in comparative and EU law research. This book will thus be essential reading for anyone wishing to understand the mutual implications of EU competition law and policy for developing national healthcare reforms. Dr Mary Guy is a Lecturer in Law at Lancaster Law School and is directing the law component of a British Academy/Leverhulme Trust-funded interdisciplinary project on 'EU Health Policy and Law - Shaping a Future Research Agenda' in 2018-2020. She is a member of the European Association of Health Law, the Society of Legal Scholars, the Socio-Legal Studies Association, the British Association of Comparative Law, and the Chartered Institute of Linguists Educational Trust.